2017
DOI: 10.1038/s41514-017-0012-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of diabetic mice with the SGLT2 inhibitor TA-1887 antagonizes diabetic cachexia and decreases mortality

Abstract: A favorable effect of an inhibitor of the sodium–glucose cotransporter 2 (SGLT2i) on mortality of diabetic patients was recently reported, although mechanisms underlying that effect remained unclear. Here, we examine SGLT2i effects on survival of diabetic mice and assess factors underlying these outcomes. To examine SGLT2i treatment effects in a model of severe diabetes, we fed genetically diabetic db/db mice a high-fat diet and then assessed outcomes including diabetic complications between SGLT2i TA-1887-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 59 publications
5
36
0
1
Order By: Relevance
“…These observations are consistent with the maintenance of β-pancreatic activity and insulin levels in diabetic mice after the SGLTi administration [31]. While body weight control has been observed in patients treated with SGLT2i [32,33], in our hands, long-term EMP treatment maintained body weight, as previously described in db/db cachectic mice treated with SGLTi [30].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These observations are consistent with the maintenance of β-pancreatic activity and insulin levels in diabetic mice after the SGLTi administration [31]. While body weight control has been observed in patients treated with SGLT2i [32,33], in our hands, long-term EMP treatment maintained body weight, as previously described in db/db cachectic mice treated with SGLTi [30].…”
Section: Discussionsupporting
confidence: 92%
“…SGLTi mechanism of action is insulin independent; however, since db/db mice are a leptin receptor functional KO model, they are severely diabetic and glucose levels cannot be normalized by EMP treatment. However, we detected that diabetic hyperinsulinemia was longer maintained after EMP treatment, in a similar trend to that previously described in SGLTi-treated db/db mice [30]. These observations are consistent with the maintenance of β-pancreatic activity and insulin levels in diabetic mice after the SGLTi administration [31].…”
Section: Discussionsupporting
confidence: 91%
“…Given the results of the trials involving SGLT2 inhibitors, that is , decreased mortality along with an increase in ketone bodies, it would be interesting to test this class of molecules in mouse models of ageing to obtain preliminary observations regarding the feasibility of inducing glucose excretion as an anti‐ageing strategy. Notably, chronic treatment with an SGLT2 inhibitor attenuates LGI and prolongs lifespan in diabetic mice fed with a high‐fat diet …”
Section: Anti‐inflammatory Effect Of Bhb and Low‐carbohydrate/low‐calmentioning
confidence: 99%
“…Notably, chronic treatment with an SGLT2 inhibitor attenuates LGI and prolongs lifespan in diabetic mice fed with a high-fat diet. 53…”
Section: Anti-inflammatory Effect Of Bhb and Low-carbohydrate/low-cmentioning
confidence: 99%
“…can also significantly reduce the risk of mortality among diabetic subjects (Sugizaki et al, 2017). Sugizaki et al (2017) demonstrated that treatment of diabetic animals by SGLT2 inhibitors of TA-1887 reduces diabetes-induced cachexia and death by improving beta cell function and insulin sensitivity in peripheral tissues.…”
Section: Sodium Glucose Cotransporter Type 2 Inhibitorsmentioning
confidence: 99%